2010
DOI: 10.1097/yco.0b013e32833ad946
|View full text |Cite
|
Sign up to set email alerts
|

Economic evidence in intellectual disabilities: a review

Abstract: Information on resource and cost implications of various treatments and support for people with intellectual disabilities is needed. Economic evaluation techniques can be used to inform decision making. We conducted a systematic review of the literature from January 2006 to February 2010. There was a paucity of economic studies in the field. Analyses assessing a wide range of outcomes alongside costs were the most widely used evaluation method in the review. There is a need for more economic studies in this ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 19 publications
0
16
0
1
Order By: Relevance
“…The authors concluded that there was no evidence of relative cost-effectiveness for either individual budgets or standard arrangements. If policy is to aspire to being evidence-based, there is an on-going requirement for rigorous cost-effectiveness research, a conclusion also reached by Romeo and Molosankwe (2010).…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that there was no evidence of relative cost-effectiveness for either individual budgets or standard arrangements. If policy is to aspire to being evidence-based, there is an on-going requirement for rigorous cost-effectiveness research, a conclusion also reached by Romeo and Molosankwe (2010).…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the results of this study provide information on the burden caused by disabilities in rural and urban households in Central Vietnam. Such economic analyses can inform decision‐makers about additional investments that are needed to improve the welfare system (Romeo & Molosankwe ). The results have policy implications, for prioritising health problems and for adjusting welfare conditions, strengthening CBR services and government support.…”
Section: Discussionmentioning
confidence: 99%
“…There are a few studies that have examined the cost of services or interventions for children with intellectual disabilities (Romeo & Molosankwe 2010). Romeo & Molosankwe (2010) found only seven studies in their review of economic evidence in intellectual disabilities which examined economic aspects of care for people with intellectual disabilities. In this article, we report on the findings of a survey of all young people with intellectual disabilities who were identified as having challenging behaviour and in transition to adult services between 2006 and 2008 in one inner London borough.…”
Section: Costs Of Carementioning
confidence: 99%
“…There are a few studies that have examined the cost of services or interventions for children with intellectual disabilities (Romeo & Molosankwe 2010). Romeo & Molosankwe (2010) found only seven studies in their review of economic evidence in intellectual disabilities which examined economic aspects of care for people with intellectual disabilities.…”
Section: Introductionmentioning
confidence: 99%